STRATEGI PENGENDALIAN KEMISKINAN DI KABUPATEN SUKABUMI - Nur handayani; Tumija Tumija (Jurnal Ilmu Pemerintahan Widya Praja, 2016)
AbstractThis study aimed to describe what needs improvement efforts and strategies need to be developed in controlling poverty in Sukabumi.The method used is descriptive method with qualitative approach. Data were collected using the method of observation, interviews and documentation as well as analyzed through editing, dataclassification, data tabulation, data tabulation.The main strategy for poverty reduction in Sukabumi is the expansion of employment and businessopportunities, empowerment, capacity building of human resources, social protection, improvement ofenvironmental quality, increased partnerships, population control.Based on the results of analysis show that efforts need to be enhanced in the implementation ofthe control strategy of poverty in Sukabumi are: the establishment of the Institute of Microeconomics,adding Development Facility art and culture., utilization kinds of metal and non-metallic minerals,increase the population of cows, chickens and ducks to meet the shortage of meat, milk and eggs,increased production of corn, increasing the role of MCC/TKSM in handling POM and Social Welfare,peningkatam participation of women in society, the addition of educational facilities., adding humanresources (medical, nonmedical and medical support) and facilities health particularly in hospitalsPelabuhanratu and Jampangkulon, improved coordination in the area of disaster management;increased knowledge to the community in the face of disaster area if at any time there, lowering thenumber of slum areas merwujudkan appropriate housing.The strategy needs to be developed in controlling poverty in Sukabumi is added vocational trainingequipment and add qualified instructors, controlling population growth ‘, increasing the Human Resources(HR) both farmer groups and government officials that there is to be able to exploit natural resourcesin accordance with local potentials and local environmental conditions, adding a source providingsufficient irrigation to anticipate the dry season, the increase in the cage and anticipate the H5N1 virus,the addition of agricultural extension workers, additional infrastructure agricultural extension, controlover productive land use, agricultural extension budget increase, fisheries and forestry; increase theinterest of young people to the field of agriculture, the provision of land for educational purposes.Keywords: efforts and poverty control strategy